THE INFLUENCE OF FINANCIAL PERFORMANCE TOWARDS COMPANIES’ VALUE THROUGH DIVIDEND POLICY AS MODERATING VARIABLE OF FOOD AND BEVERAGE COMPANIES OF INDONESIA STOCK EXCHANGE - Tamrin, Sujianto; Muslimin, Muslimin; Fattah, Vitayanti (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2022)
This research aims to determine the effect of financial performance consisting of profitability, leverage, liquidity, and activity variables on companies’ value with dividend policy as moderating in food and beverage companies on the Indonesia Stock Exchange. It was hypothesis-testing research. The sample in this research is 11 food and beverage companies on the Indonesia Stock Exchange period 2016-2020. As for the analysis technique of panel data regression, the data analysis tool uses Software Econometric Views (Eviews) version 10. The analysis results of the direct influence of financial performance consist of profitability, leverage, liquidity, and activity variables on the value of Food and Beverage companies on the Indonesia Stock Exchange period 2016-2020. Profitability has a significant positive effect on companies’ value, while leverage, liquidity and activity each have a negative and significant effect on companies’ value. The results of the indirect effect analysis conclude that dividend policy does not moderate the influence of each variable on profitability, leverage, and activity on companies’ value. However, the dividend policy moderates the influence of liquidity on the value of Food and Beverage companies on the Indonesia Stock Exchange (IDX) period 2016-2020. Keywords: Financial Performance, Profitability, Leverage, Liquidity, Activities, and Dividend Policy